Performance of certain new hybrid clones of Hevea brasiliensis in preliminary yield trials - Meenakumari T; Chandrasekhar T.R; Mydin K.K; Varghese Y.A (In: Advances and Challenges in Plant Breeding, Biotechnology and Conservation. (Eds. R.B. Smitha; R. Prakashkumar; N.S. Pradeep; K.V. Mohanan and P.V. Madhusoodanan). Malabar Botanical Garden and Institute for Plant Sciences, Kozhikode, India, pp. 97-107.)
The performance of 21 hybrid clones of rubber, Hevea brasiliensis evolved from 1986 hand pollination programme, was evaluated in two small-scale trials over a period of 18 years after planting. RRII 105 was the check clone in both trials. RRIM 600 was included as a second check clone in Trial 2. Annual growth during immature and mature phase of tapping, dry rubber yield over a period of 10 years and secondary attributes including bark structural traits, incidence of diseases and bole volume were recorded. In trial 1, mean yield of clones ranged from 17.7 to 79.6 gram tree-1 tap-1. The clone 86/772 recorded the highest dry rubber yield in the BO-1 panel (78.6 gram tree-1 tap-1) as well as over ten years of tapping (79.6 gram tree-1 tap-1) which was significantly superior to the yield of RRII 105 (40.8 and 50 gram tree-1 tap-1 respectively). Clone 86/380 was the second best performer with 56 gram tree-1 tap-1. Girth at opening ranged from 37.7 (86/789) to 62 cm (86/772). In trial 2, Clone 86/575 recorded significantly superior yield to RRII 105 and comparable yield with with RRIM 600. The range in yield was 23.2 (86/894) to 64 gram tree-1 tap-1 (86/575). Bark structural traits showed significant clonal variation in both the trials. Clones 86/772 and 86/756 registered superior clear bole volume of 0.2 m3 as against 0.1 m3 for RRII 105. Based on overall performance, four clones viz 86/772, and 86/575 with high yield and 86/380 and 86/756 with moderate yield combining desirable secondary attributes could be identified as clones in the pipeline for the final phase of evaluation.
Source Year: 2015
Keywords: Clones; Hevea brasiliensis; Rubber yield